Censura y expurgo en los incunables de la Biblioteca Histórica de la Universidad de Valencia. - MATÍAS, BÁRBARA BARBERÀ (Scripta)
The Spanish Inquisition established a systematic pattern of censorship in the sixteenth century; it maintained a force of purging until its demise seeking to impose a dominant ideology in terms of its own interests. The Historical Library of the University of Valencia keeps eight incunabula which were expurgated for various reasons and at different times. These books are a good example of the censorship activity carried out by the Inquisition, which helped to create a negative memory, harming authors, printers and readers themselves.